Oblique Pedagogical Strategies: Improv and Speculative Realism in Support of Social Justice Design Education - Watt, Trudy (My University, 2022)
This paper acknowledges the extent to which the majority of people who work in the field of architecture are white, examines the way that whiteness in the prevailing charity-service model of community-engaged design undermines meaningful social justice design, calls for dismantling white cultural dominance in architectural education, and outlines a pedagogical method that has shown some promise in uncovering blind spots caused by dominant culture belonging that commonly prevents architects from understanding the experiences of others during design analysis, especially where asymmetrical privilege exists, such as in the field of community-engaged design. With roots in improvisational theater tactics and a thinking framework from speculative realism that helps undermine defaulting to traditional hierarchies, these oblique pedagogical strategies appear to expand student capacity for open inquiry and self-reflection, revealing previously invisible biases, and may point to more meaningful social justice design with community. The hope is that this is an entry to providing transformative education in undergraduate architecture studios that creates unfettered creative space for students of color and productively reveals bias to white students. The concern remains that the tactic persists in centering white feelings of comfort in a way that erases BIPOC distress in the studio. Early experiments with this pedagogical approach showed promise in a fifth-year undergraduate capstone studio at Jefferson University focused on how architects (a largely privileged population) can form alliances with communities experiencing gentrification (a largely marginalized population) and again in a -second-year undergraduate studio deployed within a design fundamentals curriculum at the University of Wisconsin–Milwaukee School of Architecture and Urban Planning.
This paper was presented at the 2020 Schools of Thought Conference hosted by the Christopher C. Gibbs College of Architecture at the University of Oklahoma.
Keywords: community-engaged; improvisation; pedagogy; site analysis; social justice design; speculative realism